Evolutionary micro-founded technical change and the Kaldor-Verdoorn Law: Estimates from an artificial world - André Lorentz (Max Planck Institute of Economics, 2009)
This paper proposes to identify the micro-level sources for the dynamic increasing returns occurring at an aggregate level. The paper reverts to a micro model of technological change in-line with the evolutionary literature on industrial dynamics. The data generated through numerical simulations are used to identify the sources of increasing returns as measured by the Kaldor-Verdoorn Law. In this respect we also aim to provide some plausible micro-foundations to this Law. The paper shows that: (i) Dynamic increasing returns appear as an emergent property of the model; (ii) micro-characteristics of technical change, as the amplitude and the frequency of changes, as well as selection mechanisms significantly shape these increasing returns.
Keywords: B52; L11; O31; O33; O40; 330; Dynamic increasing returns; Kaldor-Verdoorn Law; technical change; evolutionary modelling